Delayed metabolic dysfunction in myocardium following exertional heat stroke in mice. (19th February 2020) - Laitano, Orlando; Garcia, Christian K.; Mattingly, Alex J.; Robinson, Gerard P.; Murray, Kevin O.; King, Michelle A.; Ingram, Brian; Ramamoorthy, Sivapriya; Leon, Lisa R.; Clanton, Thomas L.
Abstract : Key points: Exposure to exertional heat stroke (EHS) is associated with increased risk of long‐term cardiovascular disorders in humans. We demonstrate that in female mice, severe EHS results in metabolic changes in the myocardium, emerging only after 9–14 days. This was not observed in males that were symptom‐limited at much lower exercise levels and heat loads compared to females. At 14 days of recovery in females, there were marked elevations in myocardial free fatty acids, ceramides and diacylglycerols, consistent with development of underlying cardiac abnormalities. Glycolysis shifted towards the pentose phosphate and glycerol‐3‐phosphate dehydrogenase pathways. There was evidence for oxidative stress, tissue injury and microscopic interstitial inflammation. The tricarboxylic acid cycle and nucleic acid metabolism pathways were also negatively affected. We conclude that exposure to EHS in female mice has the capacity to cause delayed metabolic disorders in the heart that could influence long‐term health. Abstract: Exposure to exertional heat stroke (EHS) is associated with a higher risk of long‐term cardiovascular disease in humans. Whether this is a cause‐and‐effect relationship remains unknown. We studied the potential of EHS to contribute to the development of a 'silent' form of cardiovascular disease using a preclinical mouse model of EHS. Plasma and ventricular myocardial samples were collected over 14 days of recovery. Male and female C57bl/6J mice underwent forced wheel running for 1.5–3 h in a 37.5°C/40% relative humidity until symptom limitation, characterized by CNS dysfunction. They reached peak core temperatures of 42.2 ± 0.3°C. Females ran ∼40% longer, reaching ∼51% greater heat load. Myocardial and plasma samples ( n = 8 per group) were obtained between 30 min and 14 days of recovery, analysed using metabolomics/lipidomics platforms and compared to exercise controls. The immediate recovery period revealed an acute energy substrate crisis from which both sexes recovered within 24 h. However, at 9–14 days, the myocardium of female mice developed marked elevations in free fatty acids, ceramides and diacylglycerols. Glycolytic and tricarboxylic acid cycle metabolites revealed bottlenecks in substrate flow, with build‐up of intermediate metabolites consistent with oxidative stress and damage. Males exhibited only late stage reductions in acylcarnitines and elevations in acetylcarnitine. Histopathology at 14 days showed interstitial inflammation in the female hearts only. The results demonstrate that the myocardium of female mice is vulnerable to a slowly emerging metabolic disorder following EHS that may harbinger long‐term cardiovascular complications. Lack of similar findings in males may reflect their lower heat exposure. Key points: Exposure to exertional heat stroke (EHS) is associated with increased risk of long‐term cardiovascular disorders in humans. We demonstrate that in female mice, severe EHS results in metabolic changes in the myocardium, emerging only after 9–14 days. This was not observed in males that were symptom‐limited at much lower exercise levels and heat loads compared to females. At 14 days of recovery in females, there were marked elevations in myocardial free fatty acids, ceramides and diacylglycerols, consistent with development of underlying cardiac abnormalities. Glycolysis shifted towards the pentose phosphate and glycerol‐3‐phosphate dehydrogenase pathways. There was evidence for oxidative stress, tissue injury and microscopic interstitial inflammation. The tricarboxylic acid cycle and nucleic acid metabolism pathways were also negatively affected. We conclude that exposure to EHS in female mice has the capacity to cause delayed metabolic disorders in the heart that could influence long‐term health.